The Regulation of the Ownership of Flats by Foreigners after the Enactment of the Job Creation Law - Salain, Made Suksma Prijandhini Devi; Palguna, I Dewa Gede; Widiatedja, I Gusti Ngurah Parikesit (Indonesia Law Review, 2022)
The presence of foreigners in Indonesia for a long period certainly requires a place to live or a residential house. According to Article 144 (1) b of Job Creation Law, foreigners have the right to own flat units in Indonesia. Is this regulation intended to attract foreign investors? If it is yes, does not it contradictory to the “kenasionalan” principle stipulated in the Basic Agrarian Law (BAL) and other Indonesian regulations? This study is aimed to deal with those legal issues, by using the normative legal method. The result shows that the ownership right of flat units given to foreigners by the Job Creation Law is in contradiction with the “kenasionalan” principle, Article 33 paragraph (3) of the 1945 Constitution, and the BAL which only allows land/building use and lease right for foreigners. In addition, the regulation which allows the establishment of flats on land with building-use rights for a maximum of 80 (eighty) years raises a legal problem since such regulation had been revoked by the Constitutional Court of the Republic of Indonesia with its Decision Number 21-22/PUU-V/2007. Thus, the study recommends that the Government conduct a review of the regulation which allows foreigners to have ownership right to flat units under the Job Creation Law.